Viral Load and Cell Tropism During Early Latent Equid Herpesvirus 1 Infection Differ Over Time in Lymphoid and Neural Tissue Samples From Experimentally Infected Horses - Giessler, Kim S.; Samoilowa, Susanna; Soboll Hussey, Gisela; Kiupel, Matti; Matiasek, Kaspar; Sledge, Dodd G.; Liesche, Friederike; Schlegel, Jürgen; Fux, Robert; Goehring, Lutz S. (Frontiers in Veterinary Science, 2020)
Upper respiratory tract infections with Equid Herpesvirus 1 (EHV-1) typically result in a peripheral blood mononuclear cell-associated viremia, which can lead to vasculopathy in the central nervous system. Primary EHV-1 infection also likely establishes latency in trigeminal ganglia (TG) via retrograde axonal transport and in respiratory tract-associated lymphatic tissue. However, latency establishment and reactivation are poorly understood. To characterize the pathogenesis of EHV-1 latency establishment and maintenance, two separate groups of yearling horses were experimentally infected intranasally with EHV-1, strain Ab4, and euthanized 30 days post infection (dpi), (n=9) and 70 dpi (n=6). During necropsy, TG, sympathetic trunk (ST), retropharyngeal and mesenteric lymph nodes (RLn, MesLn) and kidney samples were collected. Viral DNA was detected by quantitative PCR (qPCR) in TG, ST, RLn and MesLn samples in horses 30 dpi and 70 dpi. The number of positive TG, RLn and MesLn samples was reduced when comparing horses 30 dpi and 70 dpi and the viral copy number in TG and RLn significantly declined from 30 dpi to 70 dpi. EHV-1 late gene glycoprotein B reverse transcriptase PCR and IHC results for viral protein were consistently negative, thus lytic replication was excluded in the present study. Mild inflammation could be detected in all neural tissue samples and inflammatory infiltrates mainly consisted of CD3+ T-lymphocytes (T-cells), frequently localized in close proximity to neuronal cell bodies. To identify latently infected cell types, in situ hybridization (ISH, RNAScope®) detecting viral DNA was used on selected qPCR- positive neural tissue sections. In ganglia 30 dpi, EHV-1 ISH signal was located in the neurons of TG and ST, but also in non-neuronal support or interstitial cells surrounding the neuron. In contrast, distinct EHV-1 signal could only be observed in neurons of TG 70 dpi. Overall, detection of latent EHV-1 in abdominal tissue samples and non-neuronal cell localization suggests, that EHV-1 uses T-cells during viremia as alternative route towards latency locations in addition to retrograde neuronal transport. We therefore hypothesize that EHV-1 follows the same latency pathways as its close relative human pathogen Varicella Zoster Virus.